Economics and ecology united for a sustainable world - Beaton, Russ (CRC Press, 2012)
"Preface Earth is our home, and it is in crisis. There are two sides to this crisis--our economy on the one hand, and its effect on the ecology of our home planet on the other. Our economy, the human-constructed part of our home, represents the collection of manufactured artifacts, institutions, and technologies with which the human species, over the millennia, has designed with pride and used with arrogance to wrest a material existence from a wondrously bountiful but ultimately finite planet. Despite conventional thinking in the industrialized world that typical monetary and fiscal manipulations will restore order and put us back on the path of economic growth, our economy is in danger of collapse. Furthermore, over the last few decades, we have experienced incessant globalization of the resource, manufacturing, and financial systems; and this serves to extend the threatened collapse to the entire industrialized world, and not simply to the economy of the United States. Meanwhile, the natural environment is similarly sending unmistakable warnings. Glaciers melt, oceans are becoming dangerously acidic, species become extinct, natural habitats are diminishing, and weather patterns become increasingly severe and unpredictable each year. The stress on resource systems of all kinds threatens to shrink the carrying capacity of the planet, even as we call upon it for increased contributions to support a burgeoning human population. The approach of those in power, whether their base is in the public or private sector, has historically been to particularize such problems, isolate and treat each as separate issues, and attempt band-aid measures acceptable to a public oriented to business-as-usual"-- Provided by publisher.
Keywords: Sustainable development -- Citizen participation.; Environmental economics.; Globalization -- Economic aspects.; elektronické knihy; electronic books